Captain's dinner : a shipwreck, an act of cannibalism, and a murder trial that changed legal history - Cohen, Adam (Adam Seth) (Authors Equity, 2025)
"On May 19, 1884, the yacht Mignonette set sail from England on what should have been an uneventful voyage. When their vessel sank in the Atlantic, Captain Thomas Dudley and his crew found themselves adrift in a tiny lifeboat. As days turned to weeks, they faced an unthinkable choice: starve to death or resort to cannibalism. Their decision to sacrifice the youngest, 17-year-old cabin boy Richard Parker, ignited a firestorm of controversy upon their rescue. Instead of being hailed as heroes and survivors, Dudley and his crew found themselves at the center of Regina v. Dudley and Stephens, a landmark murder trial that would establish the legal precedent that necessity cannot justify murder, a principle that continues to shape Anglo-American law today." --